Regulation of DNA methylation in lesional tissue of children with atopic dermatitis - Kartal, Demet; Dirican, Muhammed Hanefi; Taheri, Serpil; Memiş, Mehmet; Solak, Eda Öksüm; Cinar, Salih Levent; Borlu, Murat (Frontiers in Medicine, 2025)
BackgroundGenetic and epigenetic mechanisms have been shown to play a role in the pathogenesis of atopic dermatitis (AD). However, the role of genes involved in the establishment of DNA methylation has not yet been demonstrated.MethodsA total of 15 pediatric patients with AD and 15 healthy volunteers were included in this study. The mRNA gene expression levels of eight different genes involved in the regulation of DNA methylation were examined in the blood and tissue samples.ResultsThe mRNA expression levels of DNMT3A genes were significantly increased, while the mRNA expression levels of DNMT3B, TET1, and TET2 genes were statistically significantly reduced in the lesional tissue of patients compared to the control group. It was observed that the mRNA expression levels of DNMT1, DNMT3A, and TET3 genes were increased, while the mRNA expression levels of DNMT3L and TET1 genes were found to be decreased in the blood of the patients.ConclusionThe results indicated that the DNA methylation pattern in the patients was hypermethylated, especially in the lesional tissue. The data obtained may contribute to the understanding of the epigenetic regulation of AD and aid in the development of new diagnostic and treatment options.